2005
DOI: 10.1016/j.cell.2005.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Sar1p N-Terminal Helix Initiates Membrane Curvature and Completes the Fission of a COPII Vesicle

Abstract: Secretory proteins traffic from the ER to the Golgi via COPII-coated transport vesicles. The five core COPII proteins (Sar1p, Sec23/24p, and Sec13/31p) act in concert to capture cargo proteins and sculpt the ER membrane into vesicles of defined geometry. The molecular details of how the coat proteins deform the lipid bilayer into vesicles are not known. Here we show that the small GTPase Sar1p directly initiates membrane curvature during vesicle biogenesis. Upon GTP binding by Sar1p, membrane insertion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
517
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 463 publications
(536 citation statements)
references
References 38 publications
17
517
0
2
Order By: Relevance
“…It has been sug- gested that Cdc15p functions downstream of SIN in regulating septum assembly (Marks et al, 1992;Wachtler et al, 2006). Interestingly, the EFC protein family members were shown to couple membrane deformation to the actin cytoskeleton (Tsujita et al, 2006), providing a potential link to COPII vesicle biogenesis (Lee et al, 2005). Thus, we set out to investigate whether Cdc15p functioned during establishment of the polarized state of tER and Golgi during cell division.…”
Section: The Efc Domain Protein Cdc15p Is Required For Ter Recruitmenmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been sug- gested that Cdc15p functions downstream of SIN in regulating septum assembly (Marks et al, 1992;Wachtler et al, 2006). Interestingly, the EFC protein family members were shown to couple membrane deformation to the actin cytoskeleton (Tsujita et al, 2006), providing a potential link to COPII vesicle biogenesis (Lee et al, 2005). Thus, we set out to investigate whether Cdc15p functioned during establishment of the polarized state of tER and Golgi during cell division.…”
Section: The Efc Domain Protein Cdc15p Is Required For Ter Recruitmenmentioning
confidence: 99%
“…Lee et al (2005) have shown that the COPII coat proteins alone were defective in forming COPII vesicles in vitro and required Sar1p function to vesiculate lipid membranes. They suggested that the formation of membrane curvature by components other than COPII vesicle proteins might be vital to the formation of the vesicles.…”
Section: Polarization Of the Secretory Pathway To The Division Sitementioning
confidence: 99%
“…Marcus Lee, un post-doc plein d'intuition, a pensé que l'inclusion du N-terminal dans la bicouche peut déplacer les phospholipides latéralement et créer une asymétrie locale dans la surface des deux feuillets, toutà fait comme l'avait proposé Sheetz et Singer des décennies plus tôt avec l'hypothèse du (( couple double couche )) (Sheetz & Singer, 1974). Dans une série d'expériencesélégantes en collaboration avec Orci, Lee avait montré que Sar1p promeut la formation de tubules membranairesà partir de liposomes synthétiques, dépendant de l'insertion de l'hélice N-terminale amphipathique et que cette insertion est nécessaireà la formation des vésicules de COPII in vitro et au transport des protéines in vivo (Lee et al, 2005).…”
Section: Copii Est Responsable Du Bourgeonnement Vésiculaireà Partirunclassified
“…Lorsque, localement, de nombreuses protéines Sar1 s'insèrent dans le feuillet externe (côté cytoplasme), elles induisent un écartement des lipides et donc l'expansion de ce feuillet alors que la surface de l'autre feuillet reste inchangée. Pour s'accommoder de cette asymétrie, la membrane se bombe du côté cytoplasmique et acquiert une courbure définie comme positive [8]. Ensuite, le recrutement du dimère Sec23/24 par Sar1 stabilise la courbure ainsi initiée.…”
Section: Guillaume Drin Joëlle Bigay Bruno Antonnyunclassified